Thomas Merton's Creative (dis)Obedience - Ciraulo, Jonathan Martin (Cistercian studies quarterly, 2011)
The article discusses the author's view on the approach used by Anglo-American Catholic writer Thomas Merton to respond to social issues in the Catholic Church. It examines the theological and personal development of Merton, and explores his philosophy of obedience throughout his religious life. It also reflects Merton's vulnerability to obedient and disobedient character which sought personal sanctity and the better of the Catholic Church.